Finanzierung von Zukunftsinvestitionen: Pragmatische Lösungen sind gefragt; Financing investments in the future: Pragmatic solutions are needed - Monika Schnitzer; Achim Truger (Wirtschaftsdienst, 2022)
– Since the new German federal government has imposed tight fiscal policy restrictions on itself, a pragmatic approach is needed to finance the spending requirements of the transformation. The financing instruments mentioned in the coalition agreement appears to be suitable in principle for meeting key fiscal challenges facing the federal government in the coming years. However, they need to be quantified in concrete terms as quickly as possible and designed to ensure legal security in order to send reliable signals for the necessary capacity building, particularly in the construction industry and public administration.
Keywords: E62; H54; H62; 330; Finanzpolitik; Investition; Deutschland